The significance of natural phenomenon in the Malay and Chinese Peranakan Pantun(s) message reflectors - Low, Kok On; Sim, Chee Cheang (2012)
To some literary scholars,the Malay pantun(s) are probably a perfect mirror of the Malay world,and a Malay soul . Passed down orally through the generations,the pantun is a form of oral literature that finds its roots amongst a great many kinds of people .The focus of this paper is the Malay and Malaysian Chinese Peranakan pantun(s),some of which were collected directly from informants in Malacca and Singapore . The Malay pantun's penchant for nature in the first couplet of a pantun,which is reiterated in the Malaysian Chinese Peranakan pantun,becomes the focus of this analysis . Besides,it is the contention of this paper that the reiteration of nature reflectors is the?mirror effect?o f the collision between the Malay andChinese Peranakan pantun(s) .The natural phenomena presence in both types of pantun(s) emphasizes daily lives which were closely associated with the natural surroundings of the Malay and Malaysian Chinese in those days and at the same time formed the uniqueness and the beauty of their pantun(s) .